Talent management, organisational commitment, and turnover intention: implications for psychological well-being in the construction industry - Mardhiah Mohd Yunos,; Nor Diana Mohd Mahudin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Despite extensive research on talent management, its direct effects on employee commitment and well-being are often overlooked, particularly in the construction industry. This study addresses this gap by exploring the relationships between talent management practices, organisational commitment, and turnover intention among employees in the construction industry in Malaysia. An online survey was conducted with 38 private companies, yielding 91 responses (Male = 28, Female = 63). The survey measured three talent management dimensions (acquisition, development, and retention) alongside organisational commitment and turnover intention. Results showed that talent development was the most emphasised, followed by talent acquisition and retention. Although all talent management dimensions were significantly correlated with organisational commitment, only talent acquisition was a significant predictor. Notably, none of the dimensions significantly predicted turnover intention. This study contributes to the construction literature by providing insights into the factors influencing employees’ organisational commitment and turnover intention. It highlights the critical role of talent acquisition in fostering commitment while suggesting that other factors may better explain turnover intentions. Further research is recommended to explore these complexities and refine talent management strategies specific to the construction industry.